Traffic Violations by Minors: An Analysis of Impact, Causes, and Solutions - Early Hanafiah (UM Purwokerto Press, 2023)
Traffic violations committed by minors have become a serious problem in many countries. This phenomenon is worrying because it can cause traffic accidents that threaten people's lives and safety. The purpose of this research is to analyze the level of traffic violations committed by minors and the factors that influence their behavior on the road. The research method used is normative. Factors that influence children's traffic violation behavior include lack of knowledge about traffic rules, lack of parental supervision, peer influence, and ignorance about the serious consequences of traffic violations. This research provides important insights into the problem of traffic violations by minors and their implications for road safety. Collaborative efforts from the government, schools, families and the community are needed to increase children's awareness of the importance of obeying traffic rules. Effective educational programs and strict law enforcement need to be implemented to change the behavior of these children. In addition, the role of parents and better supervision can also contribute to reducing traffic violations by minors.